Non-velocity based analysis of passive ultrasonic signal for source location detection in composite plates: a pilot study - Z. M., Hafizi; Epaarachchi, J.; Che Ku Eddy Nizwan, Che Ku Husin; Lau, K. T. (IOP Publishing, 2012)
Acoustic Emission (AE) evaluation is one of the fast growing non-destructive techniques, owing to its ability to reveal in advance of any impending failure of a building structure. This capability makes the so called passive ultrasonic technique a very good tool in structural health monitoring; especially for composite structures. In metallic structures, AE technique is currently well established and able to provide accurate and consistent result. However, in composites, the challenge for a reliable AE results is huge due to the orthotropic behaviour of the materials. The present study investigates the energy attenuation of AE signals in thin composite plate and utilized the attenuation pattern into non-velocity based source location detection. Standard Hsu-Nielsen source location testing was applied on a glass fibre epoxy resin laminate and a single channel AE system was used to acquire AE signals with the support from AEWin software for signal analysis. A linear source location algorithm utilizing AE signals energy attenuation patterns was developed and tested for the composite specimen. The results revealed that the source location algorithm provides reasonably accurate results of source location for glass fibre epoxy resin laminate.